Game-Playing Culture in an Age of Capitalist Consumption: Young Taiwanese and Collectible Card Games - Lavanchawee, Sujarittanonta (Journal of Economics and Behavioral Studies, 2013)
Games-playing has historically been a form of leisure that is social and interactive in nature. As such, notwithstanding the dangers associated with gambling which may also be linked to games-playing, games have been considered a generally worthwhile activity which may have positive behavioral and educational externalities. However, in the age of advanced capitalism, games-playing has become subject to intensive marketing and advertising to promote consumption, particularly among young people who may have the time to play and some disposable income to invest in new games. One question this raises is the extent to which traditional games-playing modes and styles been affected by such marketing. This paper reports on research with a sample of Taiwanese undergraduate students investigating their consumption of games, the extent to which they use games to interact with other people and the changes of behavior with respect to games culture in recent years. A particular focus on the collectible card games segment of the gaming industry lends some focus to the findings described.